Challenging times: ethics, nursing and the COVID-19 pandemic - Sue Turale (2020)
© 2020 International Council of Nurses Globally nurses and midwives are working hard to detect cases of COVID-19, to save lives or give comfort in the face of death, to educate themselves and the public about protective measures to stop the viral spread, while still caring for those not infected with the virus. In many countries nurses are working under virtual siege from this pandemic, with not enough resources or personal protective equipment, overwhelming numbers of patients, staff shortages, underprepared health systems and supply chain failures. Nurses and other health and emergency workers are suffering physical and emotional stress, and moral distress from conflicting professional values. They are faced with unpalatable and complex ethical issues in practice, with moral conflicts, high levels of acuity and patient deaths, and long working hours. A rising number of nurses are infected with SARS-CoV-2 or dying in the line of duty. Nurses need strong moral courage, stamina and resilience to work on the front lines of the pandemic, often while separated from their loved ones.